Congenital mesenteric defects in an adult: A case report - Tamirat Bugie; Zinabu Abraham; Louis Marko; Sewnet Ejigu (Health and Social Sciences Research Institute - South Sudan (HSSRI-SS), 2023)
A congenital mesenteric defect in an adult is very rare, but can cause an internal hernia with small bowel obstruction. Awareness of congenital mesenteric defects is important to the general surgeon when faced with an acute abdominal condition. We report a case of a congenital mesenteric defect in a 40-year-old man who presented to the emergency department with acute abdominal pain. An X-ray revealed multiple air fluid levels with dilatation of small and large bowels suggestive of bowel obstruction or bowel ischaemia, or bowel perforations. He underwent an emergency laparotomy through a midline incision. A large mesenteric defect was discovered with viable small and large bowel. A primary repair of the defect was carried out. The patient had an uneventful recovery. Early diagnosis and treatment are essential to avoid bowel ischaemia and decrease the mortality and morbidity.